Formes d'appréhension des fragilités matérielles - Dominique Vinck; Mylène Tanferri; Elodie Fischer (Revue d'anthropologie des connaissances)
During the Fête des Vignerons, a centuries-old cultural event repeated every 20 to 25 years, many materials and technologies are tested and worked on to be integrated as components of a large-scale stage performance. These technologies and materials are part of the dramaturgy and constitute so many resources mobilised to create aesthetics and emotions. To do this, creative teams and technical departments push them beyond the limits established by their designers so that they also work outside of their intended uses. The proposed analysis focuses on the engagement, on the stage, of an LED carpet of unequalled dimensions. It is based on an ethnographic work of several years relating to the design and production of the scenic device and the show and in the sound, light, video, and television control rooms. It documents the forms of apprehension of the materials and the failures and surprises that they produce, considering what this floor must undergo and what it subjected to other actants than in the work of the controls which supervise it and repair it. It accounts for different forms of shared concern and the relational nature of material fragilities which emerge from the action.